2016
DOI: 10.1016/j.cub.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the Epithelial Barrier and Remodeling of Cell-Cell Junctions during Cytokinesis

Abstract: Summary Epithelial integrity and barrier function must be maintained during the complex cell shape changes that occur during cytokinesis in vertebrate epithelial tissue. Here, we investigate how adherens junctions and bicellular and tricellular tight junctions are maintained and remodeled during cell division in the Xenopus laevis embryo. We find that epithelial barrier function is not disrupted during cytokinesis and is mediated by sustained tight junctions. Using FRAP, we demonstrate that adherens junction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
193
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(210 citation statements)
references
References 66 publications
(92 reference statements)
8
193
0
1
Order By: Relevance
“…Epithelial cell turnover poses unique challenges, and simply maintaining a fluid-tight barrier during cell division requires a tight choreography between cells (for example, see Higashi et al, 2016). More complex epithelia face even greater difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cell turnover poses unique challenges, and simply maintaining a fluid-tight barrier during cell division requires a tight choreography between cells (for example, see Higashi et al, 2016). More complex epithelia face even greater difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…FRAP studies have proven to be a powerful tool to tease apart junction protein complexes, their interactions with the cytoskeleton, and how junctions remodel in response to stimuli such as changes in tension (Priya et al, 2013; Ratheesh et al, 2012; Van Itallie et al, 2016; Yonemura et al, 2010). For example, FRAP was recently used to demonstrated that plasticity of cell-cell junction structure and the linkage to actin is important for maintenance of cell-cell adhesion and barrier function when cells undergo cell-cell junction remodeling during cell division in Xenopus embryos (Higashi et al, 2016). This study showed that tension generated by the cytokinetic contractile ring is transmitted to the adherens junction, recruiting Vinculin, and stabilizing the dynamics of adherens junction proteins specifically at the division site (Higashi et al, 2016).…”
Section: Dynamic Nature Of Cell-cell Junctions and Their Linkage To Amentioning
confidence: 99%
“…For example, FRAP was recently used to demonstrated that plasticity of cell-cell junction structure and the linkage to actin is important for maintenance of cell-cell adhesion and barrier function when cells undergo cell-cell junction remodeling during cell division in Xenopus embryos (Higashi et al, 2016). This study showed that tension generated by the cytokinetic contractile ring is transmitted to the adherens junction, recruiting Vinculin, and stabilizing the dynamics of adherens junction proteins specifically at the division site (Higashi et al, 2016). …”
Section: Dynamic Nature Of Cell-cell Junctions and Their Linkage To Amentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, local activation of Rho GTPases and cytoskeletal mobilization during cell repair were first described in Xenopus oocytes and embryos (Benink & Bement, 2005; Clark et al, 2009; Mandato & Bement, 2001, 2003) and subsequently demonstrated for repair of many different cell types (Abreu-Blanco, Verboon, & Parkhurst, 2011, 2014; Kono, Saeki, Yoshida, Tanaka, & Pellman, 2012; Lin et al, 2012; McDade, Archambeau, & Michele, 2014; Nakamura, Verboon, & Parkhurst, 2017). More recently, live imaging of early Xenopus embryos has been used to investigate the dynamics of epithelial cell–cell junctions (Higashi, Arnold, Stephenson, Dinshaw, & Miller, 2016; Reyes et al, 2014), formation of cilia (Chung et al, 2014; Kim et al, 2010), and dynamic remodeling of the epithelial layer (Sedzinski, Hannezo, Tu, Biro, & Wallingford, 2016). In short, if a given cellular process occurs within several micrometers of the embryo surface, this model can be used to study it.…”
Section: Introductionmentioning
confidence: 99%